Pendugaan Persentase Rumah Tangga yang Memiliki Akses Terhadap Air Minum Layak, Sanitasi Layak, serta Rumah Layak Huni dan Terjangkau pada Level Kecamatan Di Provinsi Papua Tahun 2019 Menggunakan Model Fay Herriot Multivariat - Manda Syari Utami; Azka Ubaidillah (Seminar Nasional Official Statistics, 2022)
Access to proper drinking water, proper sanitation and affordable and livable houses is a problem that has become the focus of many countries, especially Indonesia. The success of these indicators is in line with the availability of data not only at the national, provincial, and regency/city levels but also at the smaller levels. Information on indicators is obtained from the Susenas of BPS a survey designed to estimate up to the regency/city level, so it does not meet the minimum sample requirement to estimate to the lower level. The Small Area Estimation (SAE) method can increase the effectiveness of the sample size by borrowing the power of the accompanying variable that has a relationship with the variable to be estimated. (Benavent, 2016) proposed the SAE method using the multivariate Fay Herriot EBLUP model by utilizing the correlation of the variables to be studied. This study aims to estimate and map the ownership data on access to proper drinking water, proper sanitation and affordable and livable houses at the district level in Papua. The results showed that the estimation of ownership indicators of access to proper drinking water, proper sanitation and affordable and livable housing using the multivariate Fay Herriot EBLUP method had a smaller relative standard error (RSE) compared to univariate and direct estimates.